2021
DOI: 10.1126/sciadv.abe2626
|View full text |Cite
|
Sign up to set email alerts
|

The CHD8/CHD7/Kismet family links blood-brain barrier glia and serotonin to ASD-associated sleep defects

Abstract: Sleep disturbances in autism and neurodevelopmental disorders are common and adversely affect patient’s quality of life, yet the underlying mechanisms are understudied. We found that individuals with mutations in CHD8, among the highest-confidence autism risk genes, or CHD7 suffer from disturbed sleep maintenance. These defects are recapitulated in Drosophila mutants affecting kismet, the sole CHD8/CHD7 ortholog. We show that Kismet is required in glia for early developmental and adult sleep architecture. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 83 publications
(119 reference statements)
2
11
0
Order By: Relevance
“…Moreover, people with IBD who experience constipation often have lower plasmatic levels of serotonin ( Atkinson et al, 2006 ). Recent work using Drosophila melanogaster indicates that the loss of CHD8 / CHD7 ortholog, kismet , leads to increased levels of serotonin in the brain and in the proventriculus and the anterior midgut, which can be zebrafish equivalents of the intestinal bulb and the anterior part of the mid-intestine, respectively ( Coll-Tané et al, 2021 ). Our work is in contradiction with this study regarding observed levels of serotonin in the mid-intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, people with IBD who experience constipation often have lower plasmatic levels of serotonin ( Atkinson et al, 2006 ). Recent work using Drosophila melanogaster indicates that the loss of CHD8 / CHD7 ortholog, kismet , leads to increased levels of serotonin in the brain and in the proventriculus and the anterior midgut, which can be zebrafish equivalents of the intestinal bulb and the anterior part of the mid-intestine, respectively ( Coll-Tané et al, 2021 ). Our work is in contradiction with this study regarding observed levels of serotonin in the mid-intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin has been previously shown to affect development in both mammals (80,81) and D. melanogaster [82][83][84][85][86][87][88][89][90][91]. Interestingly, patients with mutations in the autism risk gene CHD8 show defects in sleep initiation and maintenance, and mutation of the D. melanogaster ortholog kismet disrupts sleep architecture and increases serotonin labeling of the gut during development [92]. The hyper serotonergic state observed during development appear to decrease rather than increase sleep [92] in contrast to most of the reported effects of serotonin in the adult fly.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Among them, miR-1224-5p, miR-292a-5p, miR-760-3p, miR-331-3p, miR-874-3p, miR-134-5p, miR-154-3p, miR-495-3p, miR-376b-3p, and miR-299a-3p were down-regulated, whereas miR-21c, miR-135a-5p, and miR-16-5p were up-regulated. 76 Intriguingly, all these miRNAs were predicted to target ASD-linked genes, such as CHD7 77 and CLCN3 , 78 which are related to neuronal development and neuron adhesion, respectively ( Figure 2 ).…”
Section: Mirnas In Animal Models Of Asdmentioning
confidence: 99%